Improving triplet lamb survival: management practices used by commercial farmers - Erichsen, Cathrine; Coombs, Tamsin; Sargison, Neil; McCoard, Sue; Keady, Tim W. J.; Dwyer, Cathy M. (Frontiers in Veterinary Science, 2024)
Prolificacy has become an important breeding goal in sheep farming to increase farm profitability. With the adoption of improved genetics and management practices leading to increased lambing percentages, the proportion of triplet-born lambs has also increased on farms. However, mortality rates of triplet lambs are higher than for single-and twin-born lambs, and additional management inputs may be needed to support survival. The aim of this study was to identify factors that affect management practices that are considered important for triplet lamb survival by commercial farmers from the United Kingdom (UK), the Republic of Ireland (IRE) and New Zealand (NZ). An online survey was developed and disseminated to farmers in each country, focusing on farmer demographics, flock characteristics, management practices and production outcomes. A total of 448 farmers completed the survey, from the UK (n=168), IRE (n=218) and NZ (n=62). Respondents had larger flocks, higher scanning and lambing percentages than the country average for the UK and IRE. The mean percentage of triplet litters born within flocks was 9%, and lambs lost between scanning and lambing were 14% for UK, 15% for IRE and 25% for NZ respondents (P=0.063). Overall, 60% of all respondents reported to lamb indoors and 40% lambed outdoors, however NZ farmers almost exclusively lambed outdoors, whereas UK and IRE farmers lambed in both systems (P<0.001). NZ farmers were more likely to rear all triplet lambs with the ewe, whereas UK and IRE farmers were more likely to remove a lamb to rear by another ewe or artificially (P<0.001). Factors that influenced triplet lamb management practices of respondents in this study were respondent country of origin, flock size, age and gender. In general, younger respondents (P<0.001), and female respondents (P<0.05), were more likely to engage in management activities that were considered to promote better triplet lamb survival, compared to older and male respondents respectively. These practices were associated with better lamb survival reported by respondents but were less likely to be carried out when flock size increased (P<0.001). The results of this survey highlight future priorities or communication strategies needed to improve triplet lamb survival.